Phytocompounds of Curcuma longa extract are more effective against bacterial biofilm than pure curcumin only: An in-vitro and in-silico analysis - Lahiri, Dibyajit; Nag, Moupriya; Dey, Soumik; Dutta, Bandita; Sudipta Dash; RAY, RINA RANI (Kuwait Journal of Science, 2021)
The bioactive compounds are the group of secondary metabolites of plants which have a potent impact as antimicrobial and antibiofilm agent. Although Curcuma longa (turmeric), is well known for its antimicrobial activity, but question arises if curcumin , the major bioactive compound is only responsible for it or the synergistic and simultaneous contribution of more than one bioactive compounds are responsible for this antibiofilm efficacy. Present work was initiated with GC-MS analysis of the ethanolic extract of Curcuma longa (turmeric) which showed that in addition to curcumin, methyl palmitate dehydro zingerone had higher percent of availability within the extract. The in-silico studies also showed that when targeted upon Gram positive biofilm forming protein of Staphylococcus aureus (3TIP), curcumin alone had a binding constant value of -6.33 Kcal/mol but showed a value of -17.811 Kcal/mol, when acted in association with Dehydrozingerone. Similarly, the value of binding constant changed from -6.07 Kcal/mol to -23.844 Kcal/mol, when Gram negative biofilm forming protein (3ZYB) of Pseudomanas aeruginosa was acted upon by curcumin only and in association with methyl palmitate respectively. Lower minimum inhibitory concentration (MIC) and higher effectivity in reducing the bacterial quorum sensing (QS) activity of the turmeric extract than that of pure Curcumin I indicated the higher antimicrobial and antibiofilm efficiency of the extract respectively. This indicated clearly that the synergistic action of all the bioactive compounds impart the antibiofilm activity of turmeric. The result was further confirmed by the scanning electron microscopic (SEM) studies, fluorescent microscopic studies and FTIR analysis of EPS also.